Analysis of genetic variability, heritability and genetic advance for yield and yield associated traits in some promising advanced lines of rice (Progressive Agriculture, 2015)
A field experiment was conducted using twenty three rice genotypes including three check varieties during the period from June to December, 2013, at the Agronomy Field Laboratory, Department of Agronomy, Bangladesh Agricultural University, Mymensingh to study genetic variability, heritability and genetic advance (GA) for yield and yield associated traits in rice. The experiment was laid down in a randomized complete block design with three replications. Plant height, number of filled grains per panicle, days to 50% flowering, thousand grain weight, grain width and grain yield showed relatively high genotypic co-efficient of variation (GCV) and phenotypic co-efficient of variation (PCV) estimates. The PCV were higher than GCV for all eight traits indicating that they all interacted with the environment to some extent. High heritability was obtained for grain width (88.54%), followed by days to 50% flowering (87.61%), thousand grain weight (81.96%), grain length (81.94%), days to maturity (81.81%) and number of filled grains per panicle (78.19%) which indicates high heritable portion of variation. High to medium estimates of heritability and genetic advance were obtained for number of filled grains per panicle (18.97), days to 50% flowering (11.89), days to maturity (12.16) indicating the roles of additive gene action and a good scope of selection using their phenotypic performance. Considering, all of these characters, filled gains per panicle and days to 50% flowering and maturity were important yield related traits and could be used for selection in rice breeding programs.Progressive Agriculture 26:26-31, 2015